2016
DOI: 10.1159/000445881
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Predictors of Malignant Arrhythmias

Abstract: Background: Prediction and potential prevention of sudden cardiac death (SCD) due to malignant ventricular arrhythmia (MVA) represent an obvious unmet medical need. We estimated the prognostic relevance of numerous biomarkers associated with future MVA development in patients with coronary artery disease (CAD) over 2 years of follow-up. Methods: Patients with stable documented CAD (n = 97) with a mean age of 61 ± 10 years were prospectively enrolled in a single-center observational cohort study. Heart failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Barthel et al [22] documented that abnormal HRT parameters and decreased LVEF (< 30%) were found to be an independent predictor of mortality (HR, 4.5) in the ISAR (Innovative Stratification of Arrhythmic Risk) HRT study [21, 22]. Additionally, Golukhova et al [6] reported that HRT and elevated plasma brain natriuretic peptide were independent malignant ventricular arrhythmia predictors for the prospective screening of high-risk coronary artery disease patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barthel et al [22] documented that abnormal HRT parameters and decreased LVEF (< 30%) were found to be an independent predictor of mortality (HR, 4.5) in the ISAR (Innovative Stratification of Arrhythmic Risk) HRT study [21, 22]. Additionally, Golukhova et al [6] reported that HRT and elevated plasma brain natriuretic peptide were independent malignant ventricular arrhythmia predictors for the prospective screening of high-risk coronary artery disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…Heart rate turbulence (HRT) has been defined as a noninvasive prognostic method to reveal the cardiac death risk in high-risk patients [5, 6]. This method shows short-term fluctuations of RR intervals following ventricular premature beats (VPBs) [7].…”
Section: Introductionmentioning
confidence: 99%
“…The autonomic nervous system has a significant regulatory effect on heart function; in addition to heart rate, cardiac conduction properties, hemodynamics, the cellular properties of cardiac myocytes, and cardiac arrhythmogenesis are also affected by the autonomic nervous system . Distinct effects of autonomic activation have been discussed in various clinical situations and specific types of arrhythmias . Heart rate variability (HRV) analysis is among the noninvasive methods that can be used to assess cardiac autonomic activity…”
Section: Introductionmentioning
confidence: 99%
“…Sudden cardiac death may be the initial manifestation of ventricular preexcitation syndrome . Hence, early recognition of high‐risk cases is important . Holter monitoring, exercise stress test, transesophageal electrophysiological study (TEEPS) and invasive electrophysiological study (EPS) are being used for this purpose .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation